A Commitment Theory of Populism - Massimo Morelli; Antonio Nicolò; Paolo Roberti (Center for Economic Studies and ifo Institute (CESifo), 2021)
When voters' trust in politicians collapses, they demand simple policies that they can easily monitor. Disenchanted citizens therefore prefer committed delegates to politicians who propose themselves as competent policy makers but without a specific policy commitment (trustees). In a two-party competition, the unique asymmetric equilibrium is such that voters with lower interest for the common good select a committed delegate, while those with higher interest for the common good appoint a trustee. In this equilibrium, we show that the committed delegate also chooses all the strategies typically associated with populism in the literature. Hence, this paper puts forward a commitment theory of populism.
Keywords: D72; D78; 330; populism; competence; commitment; information acquisition; interest groups; moral universalism